KARAKTERISTIK MATERI AJAR BAHASA ARAB DI MADRASAH TSANAWIYAH MENURUT TAKSONOMI BLOOM - Hayati, Siti Nur; Baihaqi, Ahmad (JURNAL KAJIAN ISLAM MODERN, 2024)
Teaching materials are one of the facilities that have a great influence on the progress of learning in the classroom, because learning is based on materials. Therefore, teaching materials should meet the criteria so that they can be good teaching materials and are worthy of being taught to students. This paper will discuss the criteria for Arabic language teaching materials at the junior high school level according to Bloom's Taxonomy. This study uses a qualitative method, data collection using library methods and the technique used is content analysis. The results of this paper are to determine the characteristics of junior high school teaching materials according to Bloom's Taxonomy from the cognitive side, namely from C1-C4 and from the psychomotor side, namely from P1-P3.